APLNR is involved in ATRA‐induced growth inhibition of nasopharyngeal carcinoma and may suppress EMT through PI3K‐Akt‐mTOR signaling. Issue 11 (13th August 2019) - Liu, Yi; Liu, Qingluan; Chen, Shumin; Liu, Yijun; Huang, Yumei; Chen, Pan; Li, Xiayu; Gao, Ge; Xu, Keqian; Fan, Songqing; Zeng, Zhaoyang; Xiong, Wei; et al.
Abstract : The apelin receptor (APLNR) is a GPCR involved in many pathophysiological processes; however, the correlation between APLNR expression and nasopharyngeal carcinoma (NPC) has not been reported. In this study, we used cDNA microarray data to determine APLNR expression levels in NPC tissues. We found that APLNR expression was reduced in NPC tissues compared with noncancerous nasopharyngeal epithelial tissues. Subsequently, a large‐scale sample of 1015 tissues was used to validate this discovery and explore the relationship between APLNR expression and prognosis of NPC. Expression levels of APLNR in NPC tissues were indeed down‐regulated. Furthermore, positive expression of APLNR in NPC predicted a better prognosis (disease‐free survival: P = 0.001; overall survival: P < 0.001). Moreover, ingenuity pathway analysis revealed that an indirect interaction existed between APLNR and retinoic acid (RA) in the cancer regulatory network. Consistently, after treatment with all‐ trans ‐RA (ATRA), we found that APLNR was significantly up‐regulated in NPC cell lines (5‐8F and HNE1), and proliferation of NPC cells was inhibited. Cell cycle arrest occurred in the G0 /G1 phase. In contrast, knockdown of APLNR diminished ATRA‐induced growth inhibition of NPC cells. In addition, we surprisingly found that APLNR also played an important role in migration and invasion of NPC. Wound‐healing and Transwell assays revealed that APLNR overexpression led to reduced migratory and invasive properties in 2 NPC cell lines. Western blot results revealed that hallmarks of epithelial‐mesenchymal transition (EMT) were altered as well, suggesting that APLNR was capable of inhibiting EMT in NPC cells. Our study further demonstrated that low expression of APLNR promoted EMT in NPC cells by activating the PI3K‐protein kinase B‐mammalian target of rapamycin signaling pathway. Taken together, our data suggest that APLNR could potentially predict prognosis for patients with NPC and inhibit proliferation, migration, invasion, and EMT in nasopharyngeal cancer cells.—Liu, Y., Liu, Q., Chen, S., Liu, Y., Huang Y., Chen, P., Li, X., Gao, G., Xu, K., Fan, S., Zeng Z., Xiong W., Tan, M., Li, G., Zhang W. APLNR is involved in ATRA‐induced growth inhibition of nasopharyngeal carcinoma and may suppress EMT through PI3K‐Akt‐mTOR signaling. FASEB J. 33, 11959‐11972 (2019). www.fasebj.org